Effect of flexoelectricity and order electricity on defect cores in nematic droplets - Porenta, T; Ravnik, M; Zumer, S (2011)
Macroscopic polarization, induced in a strongly deformed nematic director field, is shown to strongly affect the stability of defect structures. We present a numerical study which addresses the role of flexoelectricity and order electricity in confined nematic liquid crystals, more specifically in nematic droplets with planar and homeotropic surface anchoring. Electrostatic potential induced by flexo- and order electricity are calculated in the droplets taking into the account full anisotropy of the nematic director profile. Potentials as high as 1 V are found in 200 nm droplets with flexoelectric constant e = 40 pC m-1. Spatial profiles of contributions to the total free energy are calculated to identify flexo- and order elasticity relevant regions. For different flexoelectric coupling strengths and different anchoring strengths, changes in the core of the defects are examined. Their stability is discussed. Finally, flexo- and order electricity driven transitions between point defect, ring defect and axial structure are demonstrated in homeotropic droplets. © 2011 The Royal Society of Chemistry.